Growth and utilization rate of yellowstripe scad (Selaroides leptolepis, Cuvier 1833) landed at Pekalongan Archipelago Fishing Port - Nadhifa, Ratna Fitri; Solichin, Anhar; Rahman, Arif (Acta Aquatica: Aquatic Sciences Journal, 2023)
Abstract Yellowstripe scad (Selaroides leptolepis) is a small pelagic fish. Yellowstripe scad is one of the catches of mini purse seine fishing gear which has important economic value. Continuous fishing activities for yellowstripe scad can disrupt the sustainability of yellowstripe scad. The purposes of this study were to determine size structure, growth parameters, length-weight relationship, size of the first caught (Lc50%), mortality rate, and utilization rate of yellowstripe scad. This research was conducted in June, July, and August 2022 at Pekalongan Archipelago Fishing Port. The data was collected by using a simple random sampling method, taking a 10% random sample of fish from one of the baskets caught by the mini purse seine boat landed at Pekalongan Archipelago Fishing Port. The data collected included total length (mmTL) and weight (gr). Data analysis used FiSAT II program with analysis ELEFAN I. The results obtained a sample of 1081 individuals with a length range of 94-152 mmTL and a weight of 9-54 grams. The size of the first caught (Lc50%) was 113.88 mmTL. The length-weight relationship of the yellowstripe scad was W = 0.0000054L3,1614 and the growth pattern was positive allometric. Von Bertalanffy growth parameters of yellowstripe scad were Lt = 158.03[1 - e(-0.56(t+0.184))] with Lˆž was 158.03 mm; K was 0.56 and t0 was -0.184 years. The total mortality (Z) of yellowstripe scad was 1.86/year; natural mortality (M) was 0.77/year and fishing mortality (F) was 1.09/year. The exploitation (E) of yellowstripe scad was 0.58 which is included in the over-exploited category.Keywords: Exploitation; Growth; Mortality; Yellowstripe scad